1957
DOI: 10.1113/jphysiol.1957.sp005779
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor responses in the foot to raising body temperature in the paraplegic patient

Abstract: Studies have been made by a number of workers on the level of the outflow from the spinal cord, of vasomotor nerves to the hind limbs in the dog (Bayliss & Bradford, 1894), and in the monkey (Geogehan, Wolf, Adair, Hare & Hinsey, 1941 It was considered that a study of the foot blood flow responses to raising body temperature in a series of patients with complete lesions of the spinal cord at various levels would provide evidence of the level of vasomotor outflow to the foot in the conscious subject. The vasomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…However, sweating response in a paraplegic is injured basically according to the level of the SCI Normell, 1974;Silver et al, 1991;Tam et al, 1978). Furthermore, SBFT which can be regarded as an index of vasodilation in the thigh is also affected by the level of the SCI (Cooper et al, 1957;Freund et al, 1984;Muraki et al, 1995;1996a, 1996b. Especially in paraplegics with high lesions, who have impaired sympathetic vasomotor function in the lower limbs, it has been suggested that skin blood flow is unchanged by exposure to a high temperature (Cooper et al, 1957;Guttmann et al, 1958;Yamasaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sweating response in a paraplegic is injured basically according to the level of the SCI Normell, 1974;Silver et al, 1991;Tam et al, 1978). Furthermore, SBFT which can be regarded as an index of vasodilation in the thigh is also affected by the level of the SCI (Cooper et al, 1957;Freund et al, 1984;Muraki et al, 1995;1996a, 1996b. Especially in paraplegics with high lesions, who have impaired sympathetic vasomotor function in the lower limbs, it has been suggested that skin blood flow is unchanged by exposure to a high temperature (Cooper et al, 1957;Guttmann et al, 1958;Yamasaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SBFT which can be regarded as an index of vasodilation in the thigh is also affected by the level of the SCI (Cooper et al, 1957;Freund et al, 1984;Muraki et al, 1995;1996a, 1996b. Especially in paraplegics with high lesions, who have impaired sympathetic vasomotor function in the lower limbs, it has been suggested that skin blood flow is unchanged by exposure to a high temperature (Cooper et al, 1957;Guttmann et al, 1958;Yamasaki et al, 2000). In the present study, at both 25°C and 33°C, paraplegics with high lesions also showed no increase in SBFT irrespective of the time duration of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Within the spinal cord the sweat fibres are said to course in close proximity with the pyramidal tracts (Hyndman & Wo1kin, 1941); generally, making allowance for numerous individual variations, sweat fibres are believed to ascend in the sym pathetic chain above T6, to descend below TIO, and to ascend and to descend between T6 and TIO ) Hyndman & Wo1kin, 1941). The upper level of the auto nomic outflow to the foot has been described to occur at LI, perhaps also at TIl and TI2 (Cooper, Ferres & Guttmann, 1957).…”
Section: Review Of Literaturementioning
confidence: 98%
“…Detailed observations of sweating, including para-and tetrap1egics, have been described in important contributions of the literature (Head & Riddoch, 1917;Riddoch, 1917-18;Guttmann & List, 1928;List & Pimenta, 1944;Cooper, Ferres & Guttmann, 1957;Roth, Trelle, Rushton & Elkins, 1959;Boshes & Bluestein, 1960). List and Peet (1937) classified sweating as 'thermoregulatory, emotional, drug, gustatory and spinal reflex'.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, when skin temperature increases beyond the neutral temperature range, active skin vasodilation occurs and blood flow to the skin increases (Kellogg et al, 1991). Cooper et al (1957) reported a significant elevation in core temperature, when the arms were exposed to high temperatures (44°C), due to lack of Advance Publication by J-STAGE Published online November 20, 2019 vasodilatation in the lower extremities of subjects with injuries at C5-T10. Moreover, there was a slight increase in vasodilatation in patients with injuries at T11-T12, whereas those with injuries at L1 and able-bodied persons had similar levels of vasodilation.…”
Section: Loss Of Heat Dissipation Due To Skin Vasomotionmentioning
confidence: 99%